Innovative Language Learning Support Utilizing Duolingo and Artificial Intelligence to Enhance English Proficiency among Students at SD IT Imam Syafii Cendekia - Elida, Yusti; Oktadela, Resy; Saleh, Syamsilasmi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to enhance the quality of English language learning in Islamic-based schools through the application of artificial intelligence (AI)–driven learning technology using the Duolingo platform. The partner institution, SD IT Imam Syafii Cendekia Pekanbaru, faces challenges in students’ low learning motivation and teachers’ limited capacity to integrate technology into their instructional practices. The program was implemented over two months, from July to September 2025, involving 70 participants consisting of teachers, student assistants, and fourth to sixth-grade pupils. The implementation method included teacher training based on the Technological Pedagogical Content Knowledge (TPACK) framework, classroom integration of Duolingo through a gamification approach, and intensive mentoring for students. Data were collected through observation, questionnaires, and pre- and post-tests to measure students’ improvement in English proficiency. The results revealed a significant increase in students’ average scores, from 54.5 to 81.3 (a 49.2% improvement), along with higher motivation and engagement levels. About 92% of students reported that Duolingo-based learning was more engaging and easier to understand, while teachers demonstrated improved digital competence and creativity in instruction.